Valacyclovir as a Therapeutic Agent in Acute Retinal Necrosis: Two Case Reports - Theodoros Empeslidis; Vasileios Konidaris; Periyasami Kumar; Somnath Banerjee; James Deane; Konstantinos T Tsaousis (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2014)
Acute retinal necrosis (ARN) is a rare, but potentially blinding disease, characterized by the clinical trial of vitreous inflammation, occlusive vasculopathy, and progressive peripheral retinal necrosis [1]. It took more than a decade after its first description for its herpetic aetiology to be discovered and antiviral therapy to become the main stay of treatment [2,3]. ARN usually presents unilaterally, however, bilateral disease has been reported in up to 35% of patients [1]. The incidence in the UK is approximately 1 case per 1.6 to 2.0 million of population per year [4]. It usually affects immune-competent hosts, although it may occur in immuno-compromised individuals. As the outcome is often poor, prompt diagnosis and treatment prevents visual loss and involvement of the fellow eye. The clinical diagnosis is based on the standard diagnostic criteria proposed by the American Uveitis Society [5]. More recently, testing of aqueous or vitreous samples for viral DNA has identified varicella zoster virus (VZV), herpes simplex virus (HSV), Epstein-Barr virus (EBV) and occasionally cytomegalovirus (CMV) as the common causative agents of ARN [6,7]. Using polymerase chain reaction (PCR) methodologies, human herpes virus 6 (HHV6) has been recently implicated in ocular inflammation [8]. The state-of-the-art pattern of treatment for ARN involves intravenous acyclovir 10 mg/kg every 8 h for 5-10 days, subsequently oral acyclovir 400-800 mg 5 times daily for another 6-12 weeks, to decrease the possibility of second eye involvement [9]. Recent studies have reported that treatment with oral valacyclovir as the sole antiviral therapy resulted in favorable outcomes, with complete resolution of retinitis, a restoration of visual acuity, and a retinal detachment rate comparable with previously reported outcomes for intravenous acyclovir [9].